Sensory hair cell death and regeneration in fishes - Monroe, Jerry D.; Rajadinakaran, Gopinath; Smith, Michael E. (Frontiers in Cellular Neuroscience, 2015)
Sensory hair cells are specialized mechanotransductive receptors required for hearing and vestibular function. Loss of hair cells in humans and other mammals is permanent and causes reduced hearing and balance. In the early 1980’s, it was shown that hair cells continue to be added to the inner ear sensory epithelia in cartilaginous and bony fishes. Soon thereafter, hair cell regeneration was documented in the chick cochlea following acoustic trauma. Since then, research using chick and other avian models has led to great insights into hair cell death and regeneration. However, with the rise of the zebrafish as a model organism for studying disease and developmental processes, there has been an increased interest in studying sensory hair cell death and regeneration in its lateral line and inner ears. Advances derived from studies in zebrafish and other fish species include understanding the effect of ototoxins on hair cells and finding otoprotectants to mitigate ototoxin damage, the role of cellular proliferation versus direct transdifferentiation during hair cell regeneration, and elucidating cellular pathways involved in the regeneration process. This review will summarize research on hair cell death and regeneration using fish models, indicate the potential strengths and weaknesses of these models, and discuss several emerging areas of future studies.